What is the Practical Significance of the Relation between Gender Equality and Ecological Balance? - Kloukina, Nagia (HAPSc Policy Briefs Series, 2020)
Nowadays it is indisputable that climate change is a global phenomenon. On the one hand, there have recently been ever-increasing efforts by the international non-governmental institutions (NGOs), including the European Union (EU), to combat climate change either through mitigation or adaptation methods or both. On the other hand, the whole “planet rescue package” is integrated within a “greener” capitalist system, from the governance of which the environmental damages actually originate as a result of the maximum possible capital accumulation at the expense of the weaker. Climate change is thus involved in a vicious circle and produces as well as maintains social discriminations. Gender inequality as a form of social discriminations is therefore involved in the same vicious circle of the neoliberal way of addressing societal problems. Recognizing the great spectrum of analyzing climate change policy within a political structure, namely capitalism, only the connection between the devastating dominance of the human over nature and the still existing marginalization of women in the modern era will be elaborated. The aim of this paper is therefore to outline and analyze the basic framework of the eco-feminist movement about the interrelated environmental degradation and the underestimation towards women, as the feminine gender symbolizes nature.